(untitled) (Albayan Scientific Journal, 2023)
Precise management plans and implementation of programs related to the sustainable use of natural resources such as soil resources need the use of appropriate tools. Field equipment and tools associated with digital technologies and their supporting materials, software and supplies, have an important and essential role in the success of all stages of planning and implementation. This study was conducted on an area of 1133 square kilometers for the Marg Basin- Libya, using the Arc GIS Desktop 10.2.2 program for geographic information systems to contribute in the sustainable management of its land resources. The current study relied on re-analyzing data obtained from previous studies to provide quantitative and descriptive information with a high degree of accuracy and clarity. The results of the study showed that 49.26% of the soils under investigation follow the type of forest soils (Alfisols), and about 29.72% follow the type of shallow limestone soils (Mollisols), while the type of arid soils (Aridisols) is about 15.05%, the less developed type of soils (Inceptisols) constitute only 0.83% of the soils under investigation. The study also found that, the arable land without complication constitutes about 43.73%, and the arable land with moderate complications (depth - compaction) is about 15.12%, while the lands with significant complications (shallowness - salinity - stoniness) for cultivation amount to 36.02%, while the lands unfit for cultivation (rocks, Buildings) are about 5.13% of the study area. It was also found that natural forests represented 44.81% of the study area, and the lands dependent on rain-fed agriculture represented 39.29%, while irrigated lands represented only 2.27% of the area of study. The availability of the required data and information will open the way widely for experts in planning and management in the field of agricultural resources, so that, they could obtain a realistic assessment of the potential of this important region and access to the best ways to exploit and use it.